Development of Smart Lapbook Media to Improve Narrative Writing Skills in Grade V Elementary School - Ananda, Pramudia; Devianty, Rina (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2025)
This study aims to develop smart lapbook media as a learning tool to improve the ability to write narrative essays. The method used is research and development (R&D) with the ADDIE model. The subjects of the study were fifth grade students in Deli Serdang Regency, with development stages that included expert validation, limited trials, and effectiveness tests. The results showed that the smart lapbook media met the criteria of very valid based on expert assessments of media, materials and language; very practical based on teacher and student responses; and very effective in improving narrative writing skills as seen from the increase in pretest and posttest scores. This media helps students understand the structure of narrative texts through attractive visual displays, while encouraging student motivation and creativity in writing. These findings indicate that smart lapbook media is an effective alternative learning media in overcoming difficulties in learning to write at the Elementary School level. The implications of this study are expected to be used as an example and developed into a more useful media to create a meaningful learning process.